Insights into the Stability and Photophysical Properties of Expanded Porphyrins Through Theoretical Calculation (Communications in Computational Chemistry, 2025)
Expanded porphyrins serve as promising candidates for MRI contrast agents and sensitizers in photodynamic therapy.In this study, we theoretically designed a series of expanded porphyrins incorporating thiophene and selenophene moieties toinvestigate their optoelectronic properties. Density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations wereperformed to assess their aromaticity, stability, and photophysical characteristics. Our results reveal that all designed moleculesexhibit superior optoelectronic performance, with enhanced aromaticity compared to conventional porphyrins. The absorptionspectra of the molecules closely resemble that of porphyrins, suggesting potential applicability in related biomedical and photonicapplications. Notably, molecule 4, featuring both a thiophene moiety and a conventional selenophene ring, demonstrates thehighest stability, an increased energy gap highest between occupied molecular orbital (HOMO) and lowest unoccupied molecularorbital (LUMO), and a planar geometry, leading to strengthened aromaticity. These findings provide valuable insights for therational design of next-generation porphyrin-based materials.
Keywords: excited state; aromaticity; stability; optoelectronic properties; expanded porphyrins